2018
DOI: 10.1097/pec.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Traumatic Brain Injury in a Dense Urban Area Served by a Helicopter Trauma Service

Abstract: An improved understanding of the epidemiology of pediatric brain injury will provide baselines for future outcome measurement and comparative analysis. This may improve service organization and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Globally, TBI is projected to be the third leading cause of death and injury by the World Health Organization in 2020 [2,5,6]. Pediatric TBI is reported to be the most common cause of injury-related death, and it commonly follows road traffic accidents and falls [7,8]. TBI accounted for 8.3% of the pediatric emergency department (ED) visits with mild severity according to the Western studies [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, TBI is projected to be the third leading cause of death and injury by the World Health Organization in 2020 [2,5,6]. Pediatric TBI is reported to be the most common cause of injury-related death, and it commonly follows road traffic accidents and falls [7,8]. TBI accounted for 8.3% of the pediatric emergency department (ED) visits with mild severity according to the Western studies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Poor TBI outcome was documented in resource-limited settings, and neurocritical protocol for prehospital care was recommended [29]. e TBI mortality rate ranged from 8% in Western settings to 21.2% in the developing regions [7,11,29]. Lack of prospective studies and injury data registries in most parts of Africa has made the assessment of TBI difficult [15].…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) amongst children is quite common, with estimates of three million affected children globally every year and 35,000 annual hospitalisations in the United Kingdom (1,2). A New Zealand birth cohort starting in 1977 showed that before the age of 26, 151 people (1%) had been admitted to hospital for TBI (3).…”
Section: Introductionmentioning
confidence: 99%
“…Globally TBI is projected to be the third leading cause of death and injury by world health organization in 2020 [2,5,6]. Pediatric TBI is reported to be the common cause of injury related death, and it commonly follows road traffic accidents and falls [7,8]. Western studies documented TBI contributing for 8.3% of pediatric emergency department(ED) visits, and commonly with mild severity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Outcome of TBI varied in resource limited settings and neurocritical protocol for prehospital care was recommended [29]. Mortality rate ranged from 8% in western settings to 21.2% in developing regions [7,11,29]. Lack of prospective studies and injury data registries in most parts of Africa has made the assessment of TBI difficult [15].…”
Section: Introductionmentioning
confidence: 99%